The Poverty Impacts of Global Commodity Trade Liberalization - Hertel, Thomas W. (World Bank, Washington, DC, 2017)
This paper examines the poverty impacts of global merchandise trade reform by looking at a wide range of developing countries in Africa, Asia and Latin America. Overall, the authors find that trade reform tends to reduce poverty primarily through the inclusion of agricultural components. The majority of developing country sample experiences small poverty increases from non-agricultural reforms. The authors explore the relative poverty-friendliness of agricultural trade reforms in detail, examining the differential impacts on real after-tax factor returns of agricultural versus non-agricultural reforms. This analysis is extended to the distribution of households by looking at stratum-specific poverty changes. The author's findings indicate that the more favorable impacts of agricultural reforms are driven by increased returns to peasant farm households' labor as well as higher returns for unskilled wage labor. Finally, the authors examine the commodity-specific poverty impacts of trade reform for this sample of countries. The authors find that liberalization of food grains and other processed foods represent the largest contributions to poverty reduction. More specifically, it is tariff reform in these commodity markets that dominates the poverty increasing impacts of wealthy country subsidy removal.